2007
DOI: 10.1007/s00441-007-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of retinaldehyde dehydrogenase 1 in the anterior pituitary glands of adult rats

Abstract: Retinoic acid (RA) plays a critical role in cell growth and tissue development and is also a regulatory factor of pituitary function. However, whether RA is generated in the pituitary gland and plays a role as a paracrine and/or autocrine factor is generally unknown. RA is synthesized from retinoids through oxidation processes. Dehydrogenases that catalyze the oxidation of retinal to RA are members of the retinaldehyde dehydrogenase (RALDH) family. Recently, we demonstrated that RALDH2 and RALDH3, but not RALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
(30 reference statements)
3
30
0
Order By: Relevance
“…We previously reported that RALDH1 mRNA is expressed in the anterior pituitary gland of adult male rats [4]. RALDH1 mRNA was expressed in a portion of the prolactin-producing cells (lactotrophs), marginal layer cells that line the hypophysial cleft and folliculostellate cells, in male rats.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We previously reported that RALDH1 mRNA is expressed in the anterior pituitary gland of adult male rats [4]. RALDH1 mRNA was expressed in a portion of the prolactin-producing cells (lactotrophs), marginal layer cells that line the hypophysial cleft and folliculostellate cells, in male rats.…”
Section: Discussionmentioning
confidence: 96%
“…We recently also reported that RALDH1 mRNA, but not RALDH2 or RALDH3 mRNA, is expressed in the anterior pituitary gland of adult rats [4]. We speculated that RA may play a role as an autocrine and/or paracrine signaling molecule in the anterior pituitary gland.…”
mentioning
confidence: 89%
See 3 more Smart Citations